FEMINIST LITERARY NOTES: Questions of Identity in Everything Good Will Come and We Need New Names. - Ruan Nunes (Departamento de História - Colégio Pedro II, 2016)
Feminism as a movement has adapted/changed as time goes by and contemporary literature produced by female African writers has recently offered a locus to assess how the movement has favoured the field. Two novels are briefly investigated in this article, namely Everything Good Will Come by Nigerian Sefi Atta and We Need New Namesby Zimbabwan NoViolet Bulwayo. My aim is to discuss how feminism, in its close-knit relationship with postcolonialism, dialogues with the aforementioned literature to offer some reflection upon the position of the woman as a doubly colonised subject, with special attention to questions of identity.